The marketplace of print : pamphlets and the public sphere in early modern England - Halasz, Alexandra (Cambridge studies in Renaissance literature and culture ;, 1997)
Early modern pamphlets serve as an important vehicle for examining print culture, particularly the historical entanglement between the technology of print and a developing capitalism. Attention to the controversies surrounding their circulation reveals that pamphlets became a focus for anxieties about print culture in general. Alexandra Halasz combines close readings of pamphlets by Robert Greene, Thomas Nashe, Gabriel Harvey, Thomas Deloney and John Taylor, among others, with a discussion of the history and deployment of print technology and its specifically English organization as a monopoly. Taking account of the theoretical and historical issues surrounding textual property, authorship and publicity, The Marketplace of Print, first published in 1997, is both a work of historical recovery and a reflection on the ongoing problems of the relationship between the marketplace and the public sphere.